2023
DOI: 10.1007/s11227-023-05332-x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of caching and classification in edge computing based on quality optimization for SDN-based IoT healthcare solutions

Abstract: This paper proposes a novel approach that uses a spectral clustering method to cluster patients with e-health IoT devices based on their similarity and distance and connect each cluster to an SDN edge node for efficient caching. The proposed MFO-Edge Caching algorithm is considered for selecting the near-optimal data options for caching based on considered criteria and improving QoS. Experimental results demonstrate that the proposed approach outperforms other methods in terms of performance, achieving decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…It also introduced KMFCM and intensity adjustment by analyzing volume. The threshold in Alzheimer’s disease was used by [ 26 ] to incorporate current and enhanced segmentation methods for MRI segmentation. Nearly all of the methodologies mentioned earlier rely upon segmentation of the MR brain image sequence, while the proposed approach promoted the clear distinction of the T1, T2, and FLAIR image sequences [ 27 ].…”
Section: Related Workmentioning
confidence: 99%
“…It also introduced KMFCM and intensity adjustment by analyzing volume. The threshold in Alzheimer’s disease was used by [ 26 ] to incorporate current and enhanced segmentation methods for MRI segmentation. Nearly all of the methodologies mentioned earlier rely upon segmentation of the MR brain image sequence, while the proposed approach promoted the clear distinction of the T1, T2, and FLAIR image sequences [ 27 ].…”
Section: Related Workmentioning
confidence: 99%
“…Retaining and attracting customers become an important issue for the practitioners of this industry. Most of the prior research of OFD focused on adopting various algorithms to enhance efficiency [3][4][5], devising pricing policies aimed at improving the profits and welfare of the platform [6], altering restaurant and menu option positions [7], or exploring the profiles of young customers [8]. Chan et al conducted a systematic literature review and identified five future areas, including technologies, behaviors and decisions of the restaurants, risk management, TBL, and post-coronavirus pandemic [9].…”
Section: Introductionmentioning
confidence: 99%